Rock Elastic Anisotropy Study by X-ray Synchrotron, Neutron Diffraction and Ultrasonic Methods. (2017) - Lokajicek, Tomas; Svitek, Tomas; Kern, Hartmut; Wenk, Hans-Rudolf
Abstract: We present a combined study of a classical rock sample from Val Malenco, Italy, by investigating the microstructure and texture with state-of-the art synchrotron X-ray, neutron diffraction methods and measuring ultrasonic velocities both with a multianvil apparatus and a novel instrument to measure P and S velocities on spheres. Petrological properties were studied by thin section analysis in three basic structural planes. We discuss advantages and disadvantages of texture measurements and compare them with ultrasonic velocities results. Elastic tensor properties (Cij parameters) can be derived from spherical velocities by inversion. From quantitative texture measurements, elastic properties can be modelled by self-consistent averaging. Comparison of experimental and model Cij parameters is done based on microstructures. Good agreement between the velocity and microstructural models is observed. Similar methods can now be applied to more complex geological materials, where anisotropy is more significant.